The teacher’s skill and creativity in using problem situations. (Multidisciplinary Journal of Science and Technology, 2024)
A teacher’s abilities can and should be manifested through creativity, which affects the personal professional trajectory, a system that reflects original approaches, technologies, and methods of educational activities. As a result, the achievement of the teacher’s creative activity will be a qualitatively new result. The article examines creativity as one of the most important components of pedagogical skills. It also reveals the main approaches to the problem of creativity as one of the characteristics of a teacher’s personality traits. It is emphasized that the teacher’s creativity is manifested in his professional activities and has a productive impact on the education and training of students.